The disruption of NMDAR/TRPM4 death signaling with TwinF interface inhibitors: a new pharmacological principle for neuroprotection - Yan, Jing; Bading, Hilmar (Pharmaceuticals, 2023)
With the discovery that the acquisition of toxic features by extrasynaptic NMDA receptors (NMDARs) involves their physical interaction with the non-selective cation channel, TRPM4, it has become possible to develop a new pharmacological principle for neuroprotection, namely the disruption of the NMDAR/TRPM4 death signaling complex. ...